Anestesi vid kastration av spädgris - Werinder, Anna (2003)
An overwhelming majority of all male piglets are castrated without anaesthesia when they are very young. In Sweden this means that approximately one and a half million piglets are castrated every year. The reason the piglets are castrated is the strong and unpleasant smell and taste, the "boar taint" that the meat from intact boars sometimes exhibits. Boar taint is chiefly cause by androstenone and skatole, two compounds that are mostly produced by sexually mature boars and are accumulated in the subcutaneous fat. All boar meat does not exhibit boar taint and all consumers are not equally sensitive to the smell. Castration without anaesthesia is painful to the piglets and is increasingly being considered an important welfare issue around the world. In Norway piglet castration without anaesthesia is illegal since August 2002 and a ban on castration of piglets will take effect in 2009. It is likely that the situation in Sweden will develop in a similar way and it is therefore very important to find alternative ways of avoiding boar taint in pork. Until a suitable method is found it is possible anaesthesia will have to be used during a transitional period. General anaesthesia is not considered possible to use in Sweden because of environmental, labour welfare safety and disease control reasons. Local anaesthesia is the most promising option today.